APPLICATION OF KEPLER'S LAWS IN PHYSICS - Xamrayeva Zamira Urinboyevna,; Xaydarova Shahzoda Salim qizi, (The American Journal of Applied Sciences, 2024)
Kepler’s laws of planetary motion provide fundamental insights into the mechanics of celestial bodies. These laws are crucial in understanding orbital mechanics, which play a significant role in modern astrophysics, satellite engineering, and space exploration. This paper presents a comprehensive exploration of the application of Kepler's laws in physics, emphasizing their relevance to both historical and contemporary scientific advancements. The study evaluates the laws' contributions to Newtonian mechanics and modern applications in satellite technology and gravitational theory.